EMOTIONAL INTELLIGENCE DAN SELF EFFICACY TERHADAP QUARTER LIFE CRISIS PADA DEWASA AWAL - Tanti Dini Lismawanti; Alfiana Indah Muslimah; Agustina Ekasari (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2022)
Quarter life crisis is an individual respond that occur on adolescent to early adult against peak of stability, constant changes, indecisive, feeling hopeless because of previous failure or dissatisfaction, negative self-assessment that frightening one self, stuck in hard time caused by many choices, become stressed on facing the problems that are getting worse, worry about interpersonal relationship, and confused about the life purpose. All of these things happen because a lot of pressure comes from society. Emotional intelligence is believed to influence quarter life crisis. Emotional responses of a person who has a quarter life crisis can be shown as anxious, frightened, and worried. Therefore, a person who can regulate their emotions while in crisis can motivate themself and develop relationships with others which will make them achieve the desired success. Self efficacy also has a big contribution to quarter life crisis. With self efficacy person who facing quarter life crisis would believe their ability to pass through this transition era and facing their problems